Rodent behavior following a dural inflammation model with anti-CGRP migraine medication treatment - Reducha, Philip V.; Bömers, Jesper P.; Edvinsson, Lars; Haanes, Kristian A. (Frontiers in Neurology, 2023)
Background Migraine is a widespread and prevalent disease with a complex pathophysiology, of which neuroinflammation and increased pain sensitivity have been suggested to be involved. Various studies have investigated the presence of different inflammatory markers in migraineurs and investigated the role of inflammation in inflammatory models with complete Freund's adjuvant (CFA) or inflammatory soup added to the dura mater. Objective The aim of the current study was to examine whether application of CFA to the dura mater would cause behavioral alterations that are migraine relevant. In addition, we investigated the potential mitigating effects of fremanezumab, a CGRP (calcitonin gene-related peptide) specific antibody, following CFA application. Methods Male Sprague-Dawley rats were randomly divided into six groups: fresh (n = 7), fresh + carprofen (n = 6), fresh + anti-CGRP (n = 6), sham (n = 7), CFA (n = 16), CFA + anti-CGRP (n = 8). CFA was applied for 15 min on a 3 × 3 mm clearing of the skull exposing the dura mater of male Sprague-Dawley rats. We applied the Light/Dark box and Open Field test, combined with the electronic von Frey test to evaluate outcomes. Finally, we observed CGRP immunoreactivity in the trigeminal ganglion. Results No differences were observed in the Light/Dark box test. The Open Field test detected behavior differences, notably that sham rats spend less time in the central zone, reared less and groomed more than fresh + carprofen rats. The other groups were not significantly different compared to sham rats, indicating that activation of the TGVS is present in sham surgery and cannot be exacerbated by CFA. However, for the allodynia, we observed specific periorbital sensitization, not observed in the sham animals. This could not be mitigated by fremanezumab, although it clearly reduced the amount of CGRP positive fibers. Conclusion CFA surgically administered to the dura causes periorbital allodynia and increases CGRP positive fibers in the trigeminal ganglion. Fremanezumab does not reduce periorbital allodynia even though it reduces CGRP positive fibers in the TG. Further work is needed to investigate whether CFA administered to the dura could be used as a non-CGRP inflammatory migraine model.